Spreadsheet index of named bookbinders in the Sotheby's auction catalogues for the sales of the Major John Roland Abbey collection, sold between 1965 and 1989 - John Hodgson (22668215) (2025)
The spreadsheet was compiled from the 11 auction catalogues of the Major John Roland Abbey collection, which was sold at Sotheby’s in 11 portions, comprising over 3000 lots, between June 1965 and June 1989. This is believed to be the first attempt to produce an index of all eleven volumes, though several of the individual catalogues contain printed indices of their specific contents. All named binders and workshops have been included. In addition, the index contains the names of selected owners associated with the extant bindings, such as Jean Grolier, Jacques Auguste de Thou, and Thomas Wotton, as well as monarchs and popes by or for whom bindings were commissioned. However, no attempt has been made to create a unified index of all owners, due to the huge effort required. Information on binders has been supplemented by reference to Charles Ramsden’s three works: French Bookbinders, 1789–1848 (1950); Bookbinders of the United Kingdom (outside London), 1780–1840 (1954); and London Bookbinders, 1780–1840 (1956). The author would be grateful for information on any errors or omissions.